The Influence of Forensic Audit and Professional Skepticism on Fraud Detection: Evidence from BPK Examiners in Papua - Dhina Alsa Ramadhani; Sumartono Sumartono (Eastasouth Institute, 2026)
Public asset misappropriation remains a critical fraud risk in Indonesian local governments, particularly in regions where asset recording, ownership documentation, and asset utilization involve complex administrative processes. This study examines the influence of forensic audit and professional skepticism on fraud detection among examiners of the Supreme Audit Institution (BPK) Representative Office of Papua Province. The study employed a quantitative associative design using a cross-sectional survey. Questionnaires were distributed to BPK examiners involved in local government asset audits, and 98 valid responses were analyzed using partial least squares structural equation modeling with SmartPLS 4.0. The measurement model met the validity and reliability criteria, with outer loadings ranging from 0.786 to 0.886, Average Variance Extracted values from 0.693 to 0.748, and composite reliability values from 0.919 to 0.937. The structural model showed that forensic audit had a positive and significant effect on fraud detection (β = 0.346; t = 3.534; p = 0.001), while professional skepticism had a stronger positive and significant effect (β = 0.456; t = 4.340; p < 0.001). The model explained 52.7% of the variance in fraud detection. These findings indicate that evidence-oriented investigative procedures and a questioning audit mindset jointly strengthen the ability of government external auditors to identify fraud in local government asset management.